The Effect of Organization Culture, Promotion and Selection on Employee Performance at PT. Amorindo Mitra Sentosa - Erika Wuderick; Demak Claudia Yosephine Simanjuntak; Doreen (Kusuma Negara Business School, 2021)
The purpose of this study was to examine and analyze the influence of organizational culture, promotion, and selection on employee performance. Employee performance is the result of the work of employees in carrying out their duties and responsibilities at work. The current decline in sales shows that there is a decline in performance in the company. Organizational culture is a collection of customs and habits owned by the company and implemented by employees in carrying out the work environment. Promotion is the transfer of a position that is higher than the previous position by the company to the position of an employee. Selection is the process of selecting employees to occupy positions in the company in accordance with the competencies they have which is the background of the problem in this study. The sampling technique used saturated sampling with a sample of 65 employees. In the partial test results, organizational culture has a positive and significant effect on employee performance, promotion has a positive and significant effect on employee performance, selection has a positive and significant effect on employee performance. In the partial test results, each of the variables of organizational culture, promotion, and selection has a positive and significant effect on employee performance.